Digital Transformation in Education A Literature Synthesis on Managerial Roles, Leadership, and Literacy - Riyanto Wujarso; Yudi Aziz; Mombang Sihite (UNIVERSITAS PAKUAN, 2026)
Digital transformation in the secondary education sector in Indonesia faces major challenges related to competency gaps and managerial readiness. This article aims to systematically analyze the role of management support, digital leadership, and digital literacy in shaping an effective digital learning environment. This study uses the Systematic Literature Review (SLR) method with the PRISMA protocol to review reputable literature from 2018 to 2025. The review results show that digital transformation is a strategic orchestration that depends on three main pillars. Management support functions as the provider of structural foundations and policies; digital leadership acts as a strategic compass in changing organizational culture; while digital literacy is a prerequisite for individuals to operate technology critically and innovatively. The synergy of these three elements confirms that the success of a digital learning environment cannot be achieved solely through the provision of physical infrastructure, but rather through the harmonious integration of system support, leadership exemplarity, and user proficiency. These findings have important implications for the development of education policies that focus more on investing in human capacity rather than just hardware. This conclusion is expected to serve as a strategic foundation for secondary school administrators to build a digital ecosystem that is inclusive, sustainable, and responsive to the challenges of the times in order to realize digital sovereignty in education in Indonesia. Keywords: Digital Transformation, Management Support, Digital Leadership, Digital Literacy, Digital Learning Environment.